STATE LEGAL POLICY ON THE RESPONSIBILITY OF GOVERNMENT AND BUSINESS CONTRACTORS IN ENVIRONMENTAL MANAGEMENT AND ENVIRONMENTAL DISPUTE RESOLUTION (Toxic Hazardous Waste Management) - Fatkhul Muin; Palmawati Tahir; Iin Ratna Sumirat; Muhmmad Hatta Roma Tampubolon; Haris Mubarak (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The issue of environmental management and the responsibilities of the government and local governments in hazardous and toxic waste management is certainly inseparable from the current existing conditions, where many industries produce hazardous waste. In the aspect of environmental management related to toxic hazardous waste, it is inseparable from environmental disputes over the management of hazardous and toxic waste. The approach of Law of the Republic of Indonesia Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, the regulation of environmental approval regulates specifically related to waste management which has an impact on environmental management in the community. The formulation of the Hazardous and Toxic Substances paradigm is a substance, energy, and/or other component that due to its nature, concentration, and/or amount, either directly or indirectly, 'can pollute and/or damage the Environment, and/or endanger the Environment, health, and the survival of humans and other living things. Therefore, from the understanding in the norm, the poor management of the waste will cause damage.  This research focuses on a legal approach and aims to analyze in depth the responsibility and environmental management of waste and environmental dispute resolution due to hazardous and toxic waste.